Fabrication and characterization of novel semolina-based antimicrobial films derived from the combination of ZnO nanorods and nanokaolin - Shima Jafarzadeh (2018)
© 2017, Association of Food Scientists & Technologists (India). This study aimed to provide novel biopolymer-based antimicrobial films as food packaging that may assist in reducing environmental pollution caused by the accumulation of synthetic food packaging. The blend of ZnO nanorods (ZnO-nr) and nanokaolin in different ratios (1:4, 2:3, 3:2 and 4:1) was incorporated into semolina, and nanocomposite films were prepared using solvent casting. The resulting films were characterized through field-emission scanning electron microscopy and X-ray diffraction. The mechanical, optical, physical, and antimicrobial properties of the films were also analyzed. The water vapor permeability of the films decreased with increasing ZnO-nr percentage, but their tensile strength and modulus of elasticity increased with increasing nanokaolin percentage. The UV transmittance of the semolina films were greatly influenced by an increase in the amount of ZnO-nr. The addition of ZnO-nr: nanokaolin at all ratios (except 1:4) into semolina reduced UV transmission to almost 0%. Furthermore, the ZnO-nr/nanokaolin/semolina films exhibited a strong antimicrobial activity against Staphylococcus aureus. These properties suggest that the combination of ZnO-nr and nanokaolin are potential fillers in semolina-based films to be used as active packaging for food and pharmaceuticals.